Allyl-functional thermoplastic additives for UV-curable flexible acrylic clear films.

Through the combination of multi-stage soft acrylate resin and branched polymer, the cost, environment and processing properties of flexible transparent plastic materials are solved, and transparent film preparation with low viscosity and high tensile properties is achieved.

JP7628970B2Active Publication Date: 2025-02-12ROHM & HAAS CO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021577908
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-05-29
Publication Date
2025-02-12
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

The existing flexible transparent plastic materials are difficult to balance between cost and environmental impact, and the multi-stage acrylate polymers are highly viscosity and difficult to form during processing. Too many unreacted double bonds in conventional branched chain acrylate polymers lead to adverse effects.

Method used

Using a multi-stage soft acrylate resin and a branched polymer containing at least two carbon-carbon double bonds of different reactive activities, a non-crosslinked branched polymer is formed by controlling the ratio of the crosslinking agent and the chain transfer agent to prepare a transparent film.

Benefits of technology

The viscosity of the resin is reduced, the processing performance is improved, the adverse reactions are reduced, the tensile performance is enhanced, and a transparent wrinkle-free film is formed after UV curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628970000001
    Figure 0007628970000001
  • Figure 0007628970000002
    Figure 0007628970000002
  • Figure 0007628970000003
    Figure 0007628970000003
Patent Text Reader

Abstract

Disclosed are compositions comprising a branched polymer that is the reaction product of reactants including a multi-stage flexible acrylic resin, one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1 to 15 weight percent, and a crosslinker in an amount of 0.1 to 15 weight percent, the weight percent being based on the total amount of reactants, with the proviso that the amount of crosslinker is within + / - 5 weight percent of the amount of chain transfer agent, and the crosslinker contains at least two carbon-carbon double bonds having different reactivities, and films thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The field of the invention is flexible acrylic resin compositions and films made from such compositions. [Background technology]

[0002] A variety of indoor and outdoor products benefit from the use of flexible, transparent, weather-resistant plastic materials. Fluorine-containing polymers and thermoplastic polyurethanes offer these characteristics but are too expensive for many end uses. Low-cost resins, such as polyvinyl chloride or polyethylene resins containing plasticizers, may not meet all performance requirements. Some of these polymers may also have undesirable environmental impacts.

[0003] Various acrylic resins have also been proposed. However, many are too hard, have a high modulus, or have low tear resistance for certain end uses. One commercially available acrylic resin contains a block copolymer of poly(methyl methacrylate) and poly(butyl acrylate) produced by anionic polymerization. These resins are flexible and resistant to blushing, but are prohibitively expensive for certain applications. Multistage acrylic polymers have been taught as an alternative (see, for example, U.S. Pat. No. 10,040,915). These materials tend to be highly viscous (melt flow index or rate in the range of 10 g / 10 min at 220° C. and 10 kg) and difficult to process for certain applications.

[0004] Branched acrylic polymers have also been proposed. For example, Isaure et al., J. Mater. Chem., 2003, 13, 2701-2710, disclose branched copolymers containing methyl methacrylate (MMA), a chain transfer agent (CTA), and ethylene glycol dimethacrylate (EGDMA). In these branched acrylic copolymers, Isaure found that up to 4.5% of the pendant double bonds from EGDMA remained unreacted. Summary of the Invention [Problem to be solved by the invention]

[0005] Disclosed herein is a composition comprising: a multi-stage flexible acrylic resin; and a branched polymer that is the reaction product of reactants including one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1 to 15 weight percent, and a crosslinker in an amount of 0.1 to 15 weight percent, the weight percents being based on the total amount of reactants, with the proviso that the amount of crosslinker is within + / - 5 weight percent of the amount of chain transfer agent, and the crosslinker contains at least two carbon-carbon double bonds of different reactivity. The branched polymer is not crosslinked.

[0006] Also disclosed herein is a film comprising a layer of the above composition, which layer is 150 microns or less, is transparent, and does not exhibit crease whitening. DETAILED DESCRIPTION OF THE INVENTION

[0007] Disclosed herein is a composition comprising a multi-stage soft acrylic resin and a branched polymer containing a crosslinker having at least two carbon-carbon double bonds with different reactivities. The inventors have found that the viscosity of the multi-stage soft acrylic resin is too high, preventing the resin from being used in certain applications, such as when it is desired to extrude very thin films or in certain injection molding applications. Increasing the processing temperature can degrade the resin. While the addition of a low molecular weight linear additive can reduce viscosity (increase the melt flow index), the inventors have found that the resulting product sometimes exhibits fluting whitening, which may indicate phase separation of the mixture. Surprisingly, the inventors have found that the disclosed branched polymer reduces viscosity without exhibiting undesirable fluting whitening. Additionally, compositions with branched polymer additives may exhibit improved tensile properties and a wider processing window compared to similar compositions with linear additives. The present inventors have also surprisingly found that branched polymers containing crosslinkers having at least two carbon-carbon double bonds with different reactivities can produce branched acrylic copolymers in which at least 80% of the pendant double bonds remain unreacted.

[0008] According to certain embodiments, the multi-stage flexible acrylic resin comprises a multi-stage sequential polymer composition including a first stage crosslinked acrylic polymer composition forming a core, one or more intermediate layer acrylic polymer compositions, and an outer layer acrylic polymer composition, and, Middle tier(s) and,The outer layers differ in one or more of the following: originating from different acrylate monomers, degree of crosslinking (the intermediate and outer layers may or may not be crosslinked), and glass transition temperature. The acrylic polymer composition is formed from a reaction mixture containing one or more hydrocarbyl acrylates or hydrocarbyl methacrylates, an optional crosslinking agent (except that some crosslinking agent is required in the core), and an optional chain transfer agent. According to certain embodiments, the multi-stage flexible acrylic resin includes a first stage that is the reaction product of one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates with one or more crosslinking monomers, graft-linking monomers, or combinations thereof. According to certain embodiments, the amount of units derived from alkyl acrylate and / or alkyl methacrylate monomers ranges from 95 to 99.9 weight percent of the first stage, and the amount of units derived from crosslinking monomers and / or graft-linking monomers ranges from 0.1 to 5 weight percent. According to certain embodiments, the first stage is crosslinked with a Tg in the range of -85 to -10°C. The first stage is sometimes referred to as the core. The resin includes one or more intermediate stage layers, each of which contains 93 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates, 0 to 5 weight percent units derived from a crosslinking monomer, a graft-linking monomer, or a combination thereof, and optionally 0 to 2.0 weight percent units derived from one or more chain transfer agents. There is a compositional gradient between the intermediate layers, such that the Tg transitions from -30°C to 70°C across the width of the intermediate region. The resin further includes an outer stage or outermost layer containing 98.5 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, and styrenic monomers, and combinations thereof, and 0 to 1.5 weight percent units derived from one or more chain transfer agents, and has a Tg between 40°C and 110°C.

[0009] The crosslinkable core comprises greater than 95 to 99.9 weight percent units derived from one or more monomers selected from the group consisting of alkyl acrylate or alkyl methacrylate monomers. All individual values ​​and subranges from 95 to 99.9 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be from a lower limit of 95, 95.5, 96, 96.5, 97, 975, 98, 98.5, 99, or 99.5 weight percent to an upper limit of 95.3, 95.8, 96.3, 96.9, 97.5, 98, 98.7, 99.4, or 99.9 weight percent. For example, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 95 to 99.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 95 to 97.5 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 97.8 to 99.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 96.5 to 97.9 weight percent.

[0010] The crosslinkable core comprises 0.1 to 5 weight percent units derived from crosslinking monomers, graftlinking monomers, or combinations thereof. All individual values ​​and subranges from 0.1 to 5 weight percent are included herein and disclosed herein, for example, the amount of units derived from crosslinking monomers, graftlinking monomers, or combinations thereof can be from a lower limit of 0.1, 0.7, 1.2, 1.9, 2.6, 3.1, 3.7, 4.4, or 4.9 weight percent to an upper limit of 0.2, 0.8, 1.4, 2.1, 2.7, 3.3, 3.8, 4.5, or 5 weight percent. For example, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 0.1 to 5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 0.5 to 2.5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 1.0 to 4.0 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination thereof can be in the range of 0.3 to 3.5 weight percent.

[0011] The crosslinkable core has a Tg of −85 to −10° C. All individual values ​​and subranges of −70 to −10° C. are included herein and disclosed herein, for example, the Tg of the crosslinkable core can be from a lower limit of −85, −80, −70, −60, −50, −40, −30, −20, or −15° C. to an upper limit of −75, −65, −55, −45, −35, −25, −17, or −10° C. For example, the Tg of the crosslinkable core can be in the range of −85 to −10° C., or alternatively, the Tg of the crosslinkable core can be in the range of −60 to −40° C., or alternatively, the Tg of the crosslinkable core can be in the range of −70 to −50° C., or alternatively, the Tg of the crosslinkable core can be in the range of −50 to −30° C.

[0012] The intermediate region includes one or more intermediate layers. All individual values ​​and subranges of one or more intermediate layers are disclosed and included herein. For example, the intermediate region can include one, two, three, four, or five intermediate layers.

[0013] Each of the intermediate layers comprises up to 100 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylate or alkyl methacrylate monomers. All individual values ​​and subranges up to 100 weight percent are included herein and disclosed herein, for example, the amount of units derived from the one or more alkyl (meth)acrylate monomers can be from the lower limit of 88.5, 89.4, 90.7, 91.8, 92.6, 93.7, 94, 94.9, 95.5, 96, 97.4, 98.1, 99.3, 99.9, or 100 weight percent. For example, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 88.5 to 100 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 90.5 to 99.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 88.5 to 94.9 weight percent, or alternatively, the amount of units derived from one or more alkyl acrylate or alkyl methacrylate monomers can be in the range of 92.5 to 96 weight percent.

[0014] Each of the intermediate layers comprises 0 to 5 weight percent of units derived from a crosslinking monomer, a graftlinking monomer, or a combination of two or more thereof. All individual values ​​and subranges are included herein and disclosed herein, for example, the amount of units derived from a crosslinking monomer, a graftlinking monomer, or a combination thereof can be from a lower limit of 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 4.5 weight percent to an upper limit of 0.2, 0.7, 1.2, 1.7, 2.5, 2.7, 3.2, 3.7, 4.2, 4.7, or 5 weight percent. For example, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 0 to 5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 0 to 2.5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 2.5 to 5 weight percent, or alternatively, the amount of units derived from crosslinking monomers, graft-linking monomers, or a combination of two or more thereof can be in the range of 2 to 4 weight percent.

[0015] Each of the intermediate layers optionally comprises 0 to 2.0 weight percent units derived from one or more chain transfer agents. All individual values ​​and subranges from 0 to 2.0 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more chain transfer agents can be from a lower limit of 0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, or 2.0 weight percent to an upper limit of 0.1, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, 1.7, or 1.9 weight percent. For example, the amount of units derived from the one or more chain transfer agents can be in the range of 0 to 2.0 weight percent, or alternatively, the amount of units derived from the one or more chain transfer agents can be in the range of 0.75 to 2.0 weight percent, or alternatively, the amount of units derived from the one or more chain transfer agents can be in the range of 0 to 0.75 weight percent, or alternatively, the amount of units derived from the one or more chain transfer agents can be in the range of 0.5 to 1.0 weight percent.

[0016] Between the intermediate layers there is a compositional gradient such that the Tg transitions from −30° C. to 70° C. across the width of the intermediate region. All individual values ​​and subranges from −30° C. to 70° C. are included herein and disclosed herein, for example, the Tg can transition from a lower limit of −30, −20, −10, 0, 10, 20, 30, 40, 50, or 60° C. to an upper limit of −25, −15, −5, 5, 15, 45, or 70° C. For example, the Tg may transition over a range of -30 to 70°C, or alternatively, the Tg may transition over a range of -10 to 30°C, or alternatively, the Tg may transition over a range of -30 to -15°C, or alternatively, the Tg may transition over a range of -25 to 0°C, or alternatively, the Tg may transition over a range of 0 to 15°C, or alternatively, the Tg may transition over a range of -15 to 55°C, or alternatively, the Tg may transition over a range of 5 to 35°C.

[0017] The outermost layer comprises 98.5 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof. All individual values ​​and subranges from 98.5 to 100 weight percent are included herein and disclosed herein, for example, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof can be from a lower limit of 98.5, 98.7, 98.9, 99.1, 99.3, 99.5, 99.7, or 99.9 weight percent to an upper limit of 98.6, 98.8, 99, 99.2, 99.4, 99.6, 99.8, or 100 weight percent. For example, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof can be in the range of 98.5 to 100 weight percent; or, alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof can be in the range of 98.5 to 100 weight percent; or, alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, and styrenic monomers, and combinations of two or more thereof can be in the range of 98.5 to 100 weight percent; Alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, styrenic monomers, and combinations of two or more thereof can be in the range of 98.5 to 100 weight percent, or alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl (meth)acrylates, styrenic monomers, and combinations of two or more thereof can be in the range of 98.5 to 99.6 weight percent, or alternatively, the amount of units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, styrenic monomers, and combinations of two or more thereof can be in the range of 96.5 to 100 weight percent.

[0018] The outermost layer comprises 0 to 1.5 weight percent units derived from one or more chain transfer agents. All individual values ​​and subranges from 0 to 1.5 weight percent are included herein and disclosed herein. For example, the amount of units derived from one or more chain transfer agents can range from a lower limit of 0, 0.2, 0.4, 0.6, 0.8, 1, 1.2, or 1.4 weight percent to an upper limit of 0.1, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, or 1.5 weight percent. For example, the amount of units derived from one or more chain transfer agents can be in the range of 0 to 1.5 weight percent, or alternatively, the amount of units derived from one or more chain transfer agents can be in the range of 0 to 0.75 weight percent, or alternatively, the amount of units derived from one or more chain transfer agents can be in the range of 0.75 to 1.5 weight percent, or alternatively, the amount of units derived from one or more chain transfer agents can be in the range of 0.3 to 1.2 weight percent.

[0019] The outermost layer has a Tg of 40° C. to 110° C. All individual values ​​and subranges from 50° C. to 110° C. are included herein and disclosed herein, for example, the Tg of the outermost layer can be from a lower limit of 40, 43, 45, 50, 60, 70, 80, 90, or 100° C. to an upper limit of 55, 65, 75, 85, 95, 105, or 110° C. For example, the Tg of the outermost layer can be in the range of 40° C. to 110° C., or alternatively, the Tg of the outermost layer can be in the range of 45° C. to 80° C., or alternatively, the Tg of the outermost layer can be in the range of 75° C. to 110° C., or alternatively, the Tg of the outermost layer can be in the range of 65° C. to 95° C.

[0020] In the above case, the Tg of the copolymer can be calculated by the Fox equation [Bulletin of the American Physical Society 1,3 Page 123 (1956)] as follows:

number

[0021] For copolymers, w1 and w2 refer to the weight fractions of the two comonomers based on the weight of the monomers charged to the reactor, and T g(1) and T g(2) refers to the glass transition temperatures of two corresponding homopolymers in degrees Kelvin. For polymers containing three or more monomers, additional terms are added (w n / T g(n) For purposes of this invention, the glass transition temperatures of homopolymers are those reported in "Polymer Handbook," edited by J. Brandrup and E.H. Immergut, Interscience Publishers, 1966; however, if that publication does not report the Tg of a particular homopolymer, the Tg of the homopolymer is measured by differential scanning calorimetry (DSC).

[0022] The alkyl in the alkyl acrylate or alkyl methacrylate can be a linear or branched alkyl group having 1 to 12 carbon atoms. Exemplary monomers include, and exemplary useful alkyl groups include, butyl acrylate, ethylhexyl acrylate, ethyl acrylate, methyl methacrylate, butyl methacrylate, and iso-octyl acrylate.

[0023] Examples of crosslinkable and / or graft-linkable monomers useful in the crosslinkable core and intermediate layers include, for example, butanediol diacrylate, butanediol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, divinylbenzene, diethylene glycol diacrylate, diethylene glycol dimethacrylate, diallyl maleate, allyl methacrylate, diallyl phthalate, triallyl phthalate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate blends thereof, and combinations of two or more thereof.

[0024] Preferably, the composition comprises the multi-stage soft acrylic resin in an amount of at least 15, 20, 30, 40, 50, 60, 70, 75, or 80 weight percent and no more than 95 or 90 weight percent, based on the total weight of the composition.

[0025] According to certain embodiments, the soft acrylic resin can be blended with another polymer, examples of which include acrylate or acrylic polymers such as poly(methyl methacrylate), polyesters, polycarbonates, polyamides, and halogenated polyolefins having at least 20 or at least 40 weight percent halogen, such as polyvinyl chloride.

[0026] The branched polymer is a reaction product of reactants including one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1 to 15 weight percent, and a crosslinker in an amount of 0.1 to 15 weight percent, the weight percent being based on the total amount of reactants.

[0027] Preferably, the chain transfer agent is present in an amount of at least 0.5 weight percent, at least 1 weight percent, at least 2 weight percent, or at least 3 weight percent. Preferably, the chain transfer agent is present in an amount of no more than 14 weight percent, no more than 13 weight percent, no more than 12 weight percent, no more than 11 weight percent, or no more than 10 weight percent.

[0028] The crosslinker is a polyfunctional unsaturated monomer containing at least two carbon-carbon double bonds with different reactivities. Preferably, the crosslinker is selected from allyl methacrylate, allyl acrylate, and combinations thereof. In allyl (meth)acrylate, the allyl group has a different reactivity from the vinyl group. Conventional crosslinkers, such as di(meth)acrylate, have carbon-carbon double bonds with the same reactivity. Using NMR spectroscopy, the inventors have found that pendant double bonds using crosslinkers with the same reactivity react almost completely during polymerization to form branch points. The crosslinker according to the present invention remains substantially unreacted; for example, at least 80% of the pendant double bonds remain unreacted after polymerization. These unreacted pendant double bonds provide additional opportunities for further grafting.

[0029] The branched polymer is not crosslinked. To avoid crosslinking, the amount of crosslinker is within + / - 5 weight percent of the amount of chain transfer agent. Preferably, the amount of crosslinker is within + / - 4 weight percent of the amount of chain transfer agent. More preferably, the amount of crosslinker is within + / - 3 weight percent of the amount of chain transfer agent.

[0030] Surprisingly, the inventors have found that the amount of crosslinker can exceed the amount of chain transfer agent while still forming a branched polymer. Crosslinkers with functional groups having similar activity will form a crosslinked polymer if the amount of crosslinker in molar terms exceeds the amount of chain transfer agent in molar terms. According to the present invention, the amount of crosslinker in molar terms can exceed the amount of chain transfer agent without forming a crosslinked polymer.

[0031] Suitable monoethylenically unsaturated ester monomers useful for making branched polymers according to certain embodiments can have the structure R'-C(O)OR, where R is a hydrocarbyl group (e.g., an alkyl group or an aryl group) and R' is a monoethylenically unsaturated aliphatic group having at least 2 or 3 carbon atoms. Preferably, R is an alkyl group of at least 1, 2, or 3 carbon atoms. According to certain embodiments, R is an alkyl group having 12, 10, 8, 6, or 5 or fewer carbon atoms. According to certain embodiments, R is an aryl group of 6 to 12 carbon atoms. According to certain embodiments, R' has 6 or fewer carbon atoms. Examples of suitable monomers include methyl acrylate, butyl acrylate, ethylhexyl acrylate, ethyl acrylate, methyl methacrylate, butyl methacrylate, cyclohexyl (meth)acrylate, cyclopentyl methacrylate, tetrahydrofurfyl methacrylate, and benzyl (meth)acrylate. Preferably, the monoethylenically unsaturated ester monomer is selected from methyl methacrylate and butyl methacrylate. A combination of two or more such monoethylenically unsaturated ester monomers can be used. For example, a combination of methyl methacrylate and butyl methacrylate can be used. For example, the amount of methyl methacrylate can be at least 20, 30, 40, 50, 60, 70, or 80 weight percent of the reactants, and can be less than 99.8, 99, 98, 97, 96, 95, 90, or 85 weight percent of the reactants. The second monoethylenically unsaturated ester monomer (e.g., butyl acrylate) can be 0 or more than 0, 1, 2, 3, 4, or 5 weight percent of the reactants, and less than 60, 50, 40, 30, 20, or 10 weight percent of the reactants. In certain embodiments, additional monoethylenically unsaturated ester monomers can be used. In such embodiments, the combination of the second and additional monoethylenically unsaturated monomer(s) taken together is greater than 0, 1, 2, 3, 4, or 5 weight percent of the reactants and less than 60, 50, 40, 30, 20, or 10 of the reactants.

[0032] According to certain embodiments, one or more additional monounsaturated addition-polymerizable (e.g., monoethylenically unsaturated) monomers may be included. For example, styrene or acrylonitrile may be added. The amount of such additional monounsaturated addition-polymerizable monomers is preferably less than 10 or 5 weight percent based on the weight of the reactants.

[0033] Preferably, the monoethylenically unsaturated ester monomer is present in the branching monomer in an amount of at least 65 weight percent, based on the total weight of the reactants forming the branching monomer, such as, for example, at least 70 weight percent, at least 75 weight percent, at least 80 weight percent, at least 85 weight percent, or at least 90 weight percent.

[0034] The reactants further include a chain transfer agent (CTA). The chain transfer agent can be any compound known or found to be useful as a chain transfer agent in the polymerization of acrylate or methacrylate monomers. For example, a thiol chain transfer agent can be used. Examples of such thiol CTAs include monofunctional and polyfunctional thiols. Monofunctional thiols include, but are not limited to, propyl mercaptan, butyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecyl mercaptan, thioglycolic acid, mercaptopropionic acid, alkyl thioglycolates such as 2-ethylhexyl thioglycolate or octyl thioglycolate, mercaptoethanol, mercaptoundecanoic acid, thiolactic acid, and thiobutyric acid. Polyfunctional thiols include trifunctional compounds such as trimethylolpropane tris(3-mercaptopropionate), tetrafunctional compounds such as pentaerythritol tetra(3-mercaptopropionate), pentaerythritol tetrathioglycolate, pentaerythritol tetrathiolactate, and pentaerythritol tetrathiobutyrate, hexafunctional compounds such as dipentaerythritol hexa(3-mercaptopropionate), dipentaerythritol hexathioglycolate, and octafunctional thiols such as tripentaerythritol octa(3-mercaptopropionate), and tripentaerythritol octathioglycolate. The use of polyfunctional thiols is a useful method for increasing the branching degree of polymers. Optionally, the chain transfer agent can include a mixture of two or more compounds. Preferably, the CTA is: [ka] .

[0035] The alternative chain transfer agent can be any species known to reduce molecular weight in conventional free-radical polymerization of vinyl monomers. Examples include sulfides, disulfides, and halogen-containing species. Catalytic chain transfer agents such as cobalt complexes, e.g., cobalt(II) chelates such as cobalt porphyrin compounds, are also useful chain transfer agents for the present invention. Suitable cobalt chelates are known in the art and are described in WO 98 / 04603. A particularly suitable compound is bis(borondifluorodimethylglyoximate)cobaltate(II), also known as CoBF. Catalytic chain transfer agents are generally very effective at low concentrations and can therefore be used at relatively low concentrations, e.g., <0.5 wt %, preferably <0.1 wt % (based on monofunctional monomer), compared to conventional thiol chain transfer agents. Surprisingly, we have found that catalytic chain transfer compounds based on cobalt complexes can be used very effectively in the polymerization process of the present invention to obtain soluble branched polymers at concentrations of less than 0.05% by weight (500 ppmw), for example 0.0001 to 0.01% by weight (1 to 100 ppmw), based on the monofunctional monomer.

[0036] According to certain embodiments, the crosslinking agent is allyl methacrylate (ALMA), the chain transfer agent is BMP, and the monoethylenically unsaturated ester monomer is methyl methacrylate (MMA) or butyl methacrylate (BMA). Preferably, the MMA or BMA is present in an amount of 80 to 98 weight percent, the amount of ALMA is in the range of 1 or 10 weight percent, and the amount of ALMA is in the range of 1 to 10 weight percent, based on the total weight of the MMA or BMA, BMP, and ALMA.

[0037] The branched polymers can be made using any free radical polymerization method, for example, solution, suspension, emulsion, and bulk polymerization methods can all be used. For example, conventional emulsion polymerization can be used.

[0038] A surfactant or emulsifier may be used to form the branched polymer. Examples of emulsifiers include nonionic, anionic, and cationic emulsifiers.

[0039] Suitable nonionic emulsifiers are araliphatic or aliphatic nonionic emulsifiers, examples being ethoxylated mono-, di-, and trialkylphenols (degree of ethoxylation: 3 to 50, alkyl radical: C4-C6 10 ), ethoxylates of long-chain alcohols (ethoxylation degree: 3-100, alkyl radical: C8-C 36 ), and also polyethylene oxide / polypropylene oxide homopolymers and copolymers. These may contain alkylene oxide units copolymerized in random distribution or in the form of blocks. For example, ethylene oxide / propylene oxide block copolymers are very suitable. Ethoxylates of long-chain alkanols (alkyl radicals C1-C 30 It is preferable to use linear C 12 -C 20 Those with alkyl radicals and an average degree of ethoxylation of 10 to 50, as well as ethoxylated monoalkylphenols, are also particularly preferred.

[0040] Suitable anionic emulsifiers are, for example, alkyl sulfates (alkyl radical: C-C 22 ), ethoxylated alkanol (ethoxylation degree: 2 to 50, alkyl radical: C 12 -C 18 ) and ethoxylated alkylphenols (ethoxylation degree: 3-50, alkyl radical: C4-C9), sulfuric acid monoesters, alkylsulfonic acids (alkyl radical: C 12 -C 18 ), and alkylarylsulfonic acids (alkyl radical: C9-C 18Further suitable emulsifiers are described in Houben-Weyl, Methoden der organischen Chemie, volume XIV / 1, Makromolekulare Stoffe, Georg-Thieme-Verlag, Stuttgart, 1961, pp. 192-208. Also suitable as anionic emulsifiers are bis(phenylsulfonic acid) ethers and phenylsulfonic acid ethers having C4-C in one or both aromatic rings. 24 These compounds, for example from U.S. Pat. No. 4,269,749, are well known and commercially available, for example in the form of Dowfax™ 2A1 (Dow Chemical Company).

[0041] Suitable cationic emulsifiers are preferably quaternary ammonium halides, such as trimethylcetylammonium chloride, methyltrioctylammonium chloride, benzyltriethylammonium chloride, or N-C6-C 20 quaternary compounds of -alkylpyridines, -morpholines or -imidazoles, such as N-laurylpyridinium chloride.

[0042] The amount of emulsifier (or surfactant) can be at least 0.01 or 0.1 weight percent to 10 or 5 weight percent based on the amount of monomers polymerized in forming the branched polymer.

[0043] An initiator can be used to form the branched polymer. Examples of initiators can be initiated by any suitable method that generates free radicals, such as by thermally induced decomposition of a thermal initiator such as an azo compound, peroxide, or peroxyester. Therefore, the polymerization mixture also preferably contains a polymerization initiator, which can be any of those known and conventionally used in free radical polymerization reactions. Examples of azo initiators include azobis(isobutyronitrile) (AIBN), azobis(2-methylbutyronitrile), azobis(2,4-dimethylvaleronitrile), and azobis(4-cyanovaleric acid). Examples of peroxide and peroxy initiators include hydrogen peroxide, sodium peroxide, potassium peroxide, t-butyl hydroperoxide, cumene hydroperoxide, dilauroyl peroxide, tert-butyl peroxyneodecanoate, dibenzoyl peroxide, cumyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxydiethyl acetate, and tert-butyl peroxybenzoate. Examples of additional initiators include ammonium and / or alkali metal persulfates, sodium perborate, perphosphoric acid and its salts, potassium permanganate, and ammonium or alkali metal salts of peroxydisulfate, examples of which include alkali metal or ammonium peroxydisulfates, diacetyl peroxide, dibenzoyl peroxide, succinyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl perpivalate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl permaleinate (butyl permaleinate). permaleinate), cumene hydroperoxide, diisopropyl peroxydicarbamate, bis(o-toluoyl) peroxide, didecanoyl peroxide, dioctanoyl peroxide, dilauroyl peroxide, tert-butyl perisobutyrate, tert-butyl peracetate, di-tert-amyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, 2,2'-azobis(2-amidino-propane) dihydrochloride, or 2,2'-azobis(2-methylbutyronitrile).Mixtures of these initiators are also suitable. It is also possible to use reduction / oxidation (i.e., redox) initiator systems as initiators. Redox initiator systems consist of at least one, usually inorganic, reducing agent and one organic or inorganic oxidizing agent. The oxidizing component includes, for example, the emulsion polymerization initiators already identified above. The reducing component includes, for example, alkali metal salts of sulfite, such as sodium sulfite or sodium bisulfite, alkali metal salts of disulfite, such as sodium disulfite, bisulfite adducts of aliphatic aldehydes and ketones, such as acetone bisulfite, or hydroxymethanesulfinic acid and its salts, or ascorbic acid. Redox initiator systems can be used with soluble metal compounds whose metal components can exist in multiple valence states. Typical redox initiator systems are, for example, ascorbic acid / iron(II) sulfate / sodium peroxodisulfate, tert-butyl hydroperoxide / sodium disulfite, tert-butyl hydroperoxide / Na hydroxymethanesulfinate. Individual components, such as reducing components, can also be mixtures, for example a mixture of the sodium salt of hydroxymethanesulfinic acid and sodium disulfite.

[0044] The amount of initiator is generally at least 0.01 or 0.05 or 0.01 weight percent to 10 or 5 or 3 weight percent based on all monomers being polymerized.

[0045] Branched polymers are not crosslinked. This can be shown, for example, by assessing the solubility of the polymer in a solvent such as tetrahydrofuran. Crosslinked polymers are not soluble.

[0046] Branched polymers according to certain embodiments may be characterized by a polymer branching ratio g' of less than 1, 0.95, 0.9, or 0.8. According to some embodiments, g' is at least 0.5, 0.6, or 0.7. The polymer branching ratio (g') is determined by the ratio of the branched polymer ([η]) measured at each elution volume increment in gel permeation chromatography (GPC) analysis. 分岐) is compared with that of a linear polymer ([η] 直鎖状 ) to the intrinsic viscosity (Equation 1). For linear polymers, the g' value is equal to 1, and for branched polymers, g' is less than 1.

number

[0047] Molecular weight analysis: absolute molecular weight of polymer (M w , M n ), PMMA relative molecular weight (M w_PMMA , M n_PMMA ), intrinsic viscosity ([η] w , [η] nThe chromatographic resolution (λ) and branching ratio (g') can be measured by gel permeation chromatography using an online multi-angle light scattering (MALS) detector, a viscometer (VS), and a differential refractive index (dRI) detector. For example, a GPC setup can include an Agilent 1200 Series HPLC system (degasser, pump, autosampler, column oven), a Wyatt HELEOS II MALS detector, a Wyatt ViscoStar II viscometer, and a Wyatt T-rEX dRI detector. Polymer separation can be performed, for example, with a column set containing two PLgel mixed-B LS columns (10 μm particle size, 7.5 × 300 mm length) using tetrahydrofuran (THF) as the mobile phase at a flow rate of 1 mL / min. The column oven temperature is set to 30 °C. A set of 10-point PMMA standards (Agilent EasiCal PM-1) is used to calibrate the GPC column and obtain the PMMA relative molecular weight. Absolute molecular weights are obtained from MALS detection using the Zimm format, and intrinsic viscosity data are obtained from the viscometer. High molecular weight fraction data (PMMA relative molecular weights above 6500 Da) are used to calculate average g' values. For consistency in g' calculations, a linear PMMA model from the Mark-Houwink equation (Equation 2, where K = 0.0383 mL / g and α = 0.581 for the non-BA-containing samples in Table 2, and K = 0.03044 mL / g and α = 0.615 for the BA-containing polymers in Table 2) is used to calculate the ([η]) in Equation 1 using the M data from MALS detection. 直鎖状 ) is obtained.

number

[0048] The weight average molecular weight M of the branched polymer measured by GPC wAccording to certain embodiments, the molecular weight is in the range of at least 2,500, 3,000, 5,000, 10,000, 20,000, or 25,000 g / mol. According to certain embodiments, the weight average molecular weight is not more than 75,000 or 50,000 g / mol. According to certain embodiments, the number average molecular weight M of the branched polymer, as measured by GPC, is n is at least 1,250 or 1,500 g / mol. According to certain embodiments, the number average molecular weight is not more than 6,000 or 5,000 or 4,500 g / mol.

[0049] According to one particular embodiment, the branched structure is a dendritic structure.

[0050] According to certain embodiments, the amount of branched polymer in the composition is at least 1, 3, 5, or 10 percent by weight. The composition can be in a concentrated form and then mixed with a soft acrylic resin polymer to obtain the desired amount of branched polymer in the composition to be processed (e.g., extruded, injection molded). In concentrated form, the amount of branched polymer can constitute a significant portion of the composition, for example, up to 60, 50, or 40 percent by weight. To take advantage of a higher melt flow index (lower viscosity) for use in processing, according to certain embodiments, the composition can include an amount of branched polymer of up to 30, 25, or 20 percent by weight. The branched polymer is soluble (miscible) in the soft acrylic resin in the amount used so that the composition is shown to be transparent.

[0051] The composition can be made by blending the components. According to one embodiment, the components can be cold blended (e.g., mixing two aqueous latexes) and then freeze-dried or solidified. According to another embodiment, the components can be mixed in powder form.

[0052] The compositions have favorable melt flow indices making them useful for extrusion, calendering, and injection molding applications.

[0053] The composition can be crosslinked using a UV initiator. For example, the composition can contain a UV initiator and be extruded to form a film. The resulting film can then be irradiated with UV light to crosslink the composition. Without wishing to be bound by theory, it is believed that the unreacted pendant double bonds of the crosslinker in the branched polymer can graft the branched polymer to the flexible acrylic resin.

[0054] The composition may further contain additional additives desired in the final product. Examples of such additives include UV light stabilizers and antioxidants. According to certain embodiments, the additives are selected so that the composition remains transparent. Examples of UV light stabilizers include benzophenones, benzotriazoles, triazines, benzoxazinones, hindered amine light stabilizers (HALS), and hindered benzoates. Commercially available UV and light stabilizers are exemplified by Cyasorb light absorbers and light stabilizers from Solvay, Cyasorb Cynergy Solutions, TINUVIN from BASF, LowLite from Chemtura, OnCap from PolyOne, and Light Stabilizer 210 from EI du Pont de Nemours and Company of Delaware, USA. Examples of antioxidants include phenolic antioxidants and combinations of phenolic antioxidants with phosphites, thioethers, or organic sulfides. Phenolic antioxidants include fully hindered and partially hindered phenols; and sterically hindered amines such as tetramethyl-piperidine derivatives. Suitable phenolic antioxidants include vitamin E and IRGANOX™ 1010 from BASF. IRGANOX™ 1010 contains pentaerythritol tetrakis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate). Additional examples of antioxidants include acetylcysteine, arbutin, ascorbic acid, ascorbic acid polypeptide, ascorbyl dipalmitate, ascorbyl methylsilanol pectinate, ascorbyl palmitate, ascorbyl stearate, BHA, p-hydroxyanisole, BHT, t-butylhydroquinone, caffeic acid, Camellia sinensis, and the like.sinensis oil, chitosan ascorbate, chitosan glycolate, chitosan salicylate, chlorogenic acid, cysteine, cysteine ​​HCl, decyl mercaptomethylimidazole, erythorbic acid, diamylhydroquinone, di-t-butylhydroquinone, dicetyl thiodipropionate, dicyclopentadiene / t-butylcresol copolymer, digalloyl trioleate, dilauryl thiodipropionate, dimyristyl thiodipropionate, dioleyl tocopheryl methylsilanol, isoquercitrin, diosc. amine, disodium ascorbyl sulfate, disodium rutinyl disulfate, distearyl thiodipropionate, ditridecyl thiodipropionate, dodecyl gallate, ethyl ferulate, ferulic acid, hydroquinone, hydroxylamine HCl, hydroxylamine sulfate, isooctyl thioglycolate, kojic acid, madecassicoside, magnesium ascorbate, magnesium ascorbyl phosphate, melatonin, methoxy-PEG-7 rutinyl succinate Rutinyl succinate, Methylene Di-t-Butylcresol, Methylsilanol Ascorbate, Nordihydroguaiaretic Acid, Octyl Gallate, Phenylthioglycolic Acid, Phloroglucinol, Potassium Ascorbyl Tocopheryl Phosphate, Thiodiglycolamide, Potassium Sulfite, Propyl Gallate, Rosmarinic Acid, Rutin, Sodium Ascorbate, Sodium Ascorbyl / Cholesteryl Phosphate, Sodium Bisulfite, Sodium Erythorbate, Sodium Metabisulfite, Sodium Sulfite, Sodium Thioglycolate, Sorbityl Furfural, Tea Tree (Melaleucaaftemifolia) oil, tocopheryl acetate, tetrahexyldecyl ascorbate, tetrahydrodiferuloylmethane, tocopheryl linoleate / oleate, thiodiglycol, tocopheryl succinate, thiodiglycolic acid, thioglycolic acid, thiolactic acid, thiosalicylic acid, thiotaurine, retinol, tocophereth-5, tocophereth-10, tocophereth-12, tocophereth-18, tocophereth-50, tocopherol, tocophersolan, tocopheryl linoleate, tocopheryl nicotinate, tocoquinone, o-tolylbiguanide, tris(nonylphenyl)phosphite, ubiquinone, zinc dibutyldithiocarbamate, and mixtures thereof. According to certain embodiments, the total amount of additives (if any) used is less than 10, 5, or 3 weight percent based on the total weight of the composition.

[0055] According to certain embodiments, the composition is not hazy, e.g., the turbidity, as measured by light transmittance, is less than 1% when measured according to ASTM D1003 using a suitable device, e.g., BYK HazeGuard Plus.

[0056] According to some embodiments, the composition is extruded into a thin film. The film may have a thickness of 150, 125, or 100 microns or less. According to certain embodiments, the thickness is at least 50 microns. According to some embodiments, the composition is coextruded as a layer of a multilayer film. The layer may have a thickness of 150, 125, or 100 microns or less. According to certain embodiments, the layer has a thickness of at least 10, 20, 30, or 50 microns. The film is transparent. The film does not exhibit flute whitening. [Example]

[0057] Synthesis of branched polymer additives The branched polymer additive was formed by emulsion polymerization. The emulsion polymerization was carried out in a 5-liter, four-neck round-bottom flask equipped with a mechanical stirrer, heating mantle, thermometer, temperature controller, and N2 inlet. The reactor was charged with 1530 parts deionized water, 54.55 parts Na-dodecylbenzenesulfonate surfactant (DS-4, 22% in water), 0.146 parts FeSO4, and 0.16 parts acetic acid. The reactor contents were heated to 60°C with an N2 sweep. A monomer emulsion was prepared by mixing 234 parts deionized water, 18.18 parts DS-4 surfactant (22% in water), 53 parts allyl methacrylate (ALMA), 696 parts methyl methacrylate (MMA), and 52 parts butyl 3-mercaptopropionate. Nate ( The monomer emulsion was prepared in separate vessels using a t-butyl hydroperoxide (t-BHP) emulsion. Mechanical agitation was applied to effect the emulsification. The total monomer emulsion was 1,000 parts. The redox initiator system consisted of two separate solutions. The first was a 3% (by weight) solution of t-butyl hydroperoxide (t-BHP) in water (oxidizer), and the second was a 3% (by weight) solution of sodium formaldehyde sulfoxylate (SFS) in water (reducer), both totaling 53.33 parts. With the reactor at 60°C, simultaneous feeds (time zero) of the t-BHP and SFS solutions were started at 0.44 parts / min (both 120 minutes of feed time), and the monomer emulsion was started at 16.67 parts / min (60 minutes of feed time). The reactor temperature was maintained at 60°C throughout the polymerization process. At the end of the monomer feed (60 minutes total reaction time from time zero), t-BHP and SFS were continued for an additional 60 minutes (120 minutes total reaction time from time zero). The reaction was then cooled to 40°C and filtered through cheesecloth. The emulsion particle size was 58 nm (by light scattering), the solids content was 30.5% (by gravimetric determination), and the residual BA and MMA monomers were both less than 10 ppm (by headspace gas chromatography). The polymer formed is identified as Example 8 in Table 1 below.

[0058] Other examples were prepared by the same process as above, varying the ratio of crosslinker (ALMA) to chain transfer agent (BMP). The glass transition temperatures in °C were determined by differential scanning calorimetry (DSC), and the solubility was determined in tetrahydrofuran (THF). The results (average of at least two samples each) are shown in Table 1 below. In Table 1, DP indicates the degree of polymerization, i.e., the number of units of each monomer. The number average molecular weight, M n was determined by GPC. [Table 1]

[0059] Examples 2, 6, 10, and 11 were determined to be crosslinked, as indicated by their low solubility in THF. Examples 1, 3, 4, 8, 9, and 12 were nearly 100% soluble in THF.

[0060] NMR spectroscopy was performed on Examples 4, 8, and 12 to determine the amount of unreacted pendant double bonds. The polymer compositions were: 13 The amount of unreacted pendant double bonds was determined based on the C NMR integral and normalized to 100%. The amount of unreacted pendant double bonds was calculated based on its double carbon at approximately 132.0 ppm. The branched ALMA content was estimated based on its side chain -OCH2 ester carbon at approximately 65.0 ppm. As shown in Table 2 below, at least 80% of the pendant double bonds remained unreacted. [Table 2]

[0061] For comparison, NMR analysis was performed on a branched polymer containing 5 weight percent BMP, 2.5 weight percent 1,4-butanediol dimethacrylate (BGDMA), 5 weight percent butyl acrylate (BA), and 87.5 weight percent MMA. As expected, approximately 4% of the pendant double bonds were unreacted in this comparative sample.

[0062] Films made with FAR and branched polymer additives Films were made with a composition containing a blend of Paraloid™ 21308XP multistage flexible acrylic resin (FAR) with a branched polymer containing 87 weight percent MMA, 6.5 weight percent BMP, and 6.5 weight percent ALMA. The composition contained 85 weight percent FAR and 15 weight percent branched polymer. To determine whether unreacted pendant double bonds reacted after UV curing, samples were extracted with THF and the swelling ratio of the polymer was determined. Two different UV initiators, Esacure KIP150, an oligomeric alpha hydroxyketone, and Omnirad 127D, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, both available from IGM Resins, were tested.

[0063] Both UV-irradiated samples showed crosslinking of the thermoplastic matrix polymer and an increase in the swelling ratio of the crosslinked phase, as shown in Table 3. The soluble fraction before irradiation includes the soluble fraction of FAR and all additives. [Table 3]

Claims

1. 1. A composition comprising: Multi-stage soft acrylic resin, a branched polymer that is the reaction product of a mixture comprising one or more monoethylenically unsaturated ester monomers, a chain transfer agent in an amount of 0.1 to 15 weight percent, and a crosslinking agent in an amount of 0.1 to 15 weight percent, wherein the weight percent is based on the total amount of said mixture, with the proviso that the amount of said crosslinking agent is within + / - 5 weight percent of the amount of said chain transfer agent, and wherein said crosslinking agent comprises at least two carbon-carbon double bonds having different reactivities; The multi-stage flexible acrylic resin is a multi-stage sequential polymer including a first stage crosslinked acrylic polymer forming a core, one or more intermediate layer acrylic polymers forming one or more intermediate layers, and an outer layer acrylic polymer forming an outer layer; the core, the intermediate layer(s), and the outer layer differ in one or more of the following: being derived from different acrylate monomers, degree of crosslinking, and glass transition temperature; the core comprises 95 to 99.9 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylate and alkyl methacrylate monomers, and 0.1 to 5 weight percent of units derived from one or more crosslinking monomers, graft linking monomers, or combinations thereof; The core has a Tg of −85 to −10° C. each of the one or more intermediate layers comprises 93 to 100 weight percent of units derived from one or more monomers selected from the group consisting of alkyl acrylates and alkyl methacrylates, 0 to 5 weight percent of units derived from a crosslinking monomer, a graft linking monomer, or a combination thereof, and 0 to 2.0 weight percent of units derived from one or more chain transfer agents; the one or more intermediate layers have a compositional gradient across the width of the one or more intermediate layers such that Tg transitions at all individual values ​​and subranges from −30° C. to 70° C.; the outer layer comprises 98.5 to 100 weight percent units derived from one or more monomers selected from the group consisting of alkyl acrylates, alkyl methacrylates, styrenic monomers, and combinations thereof, and 0 to 1.5 weight percent units derived from one or more chain transfer agents; The outer layer has a Tg of 40° C. to 110° C. The composition comprises 75 to 95 weight percent of the multi-stage soft acrylic resin and 5 to 25 weight percent of the branched polymer, based on the total weight of the composition.

2. The composition of claim 1 , wherein the branched polymer is not crosslinked.

3. 3. The composition of claim 1 or 2, wherein the one or more monoethylenically unsaturated ester monomers have the structure R'-C(O)O-R, where R is a hydrocarbyl group of 1 to 12 carbon atoms, and where R' is a monoethylenically unsaturated aliphatic group having at least 2 or 3 carbon atoms.

4. The chain transfer agent may be propyl mercaptan, butyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecyl mercaptan, thioglycolic acid, mercaptopropionic acid, alkyl thioglycolate, mercaptoethanol, mercaptoundecanoic acid, thiolactic acid, thiobutyric acid, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetra(3-mercaptopropionate), pentaerythritol tetrathioglycolate, ... The composition of any one of claims 1 to 3, wherein the mercaptopropyl ether is selected from the group consisting of erythritol tetrathiolactate, pentaerythritol tetrathiobutyrate, dipentaerythritol hexa(3-mercaptopropionate), dipentaerythritol hexathioglycolate, tripentaerythritol octa(3-mercaptopropionate), tripentaerythritol octathioglycolate, butyl 3-mercaptopropionate, and combinations of two or more thereof.

5. The composition of any one of claims 1 to 4, wherein the crosslinker is selected from the group consisting of allyl methacrylate, allyl acrylate, and combinations thereof.

6. The composition of claim 1, wherein the amount of the crosslinking agent is 3 to 10 percent by weight.

7. The composition of claim 1, wherein the amount of the chain transfer agent is from 3 to 10 percent by weight.

8. The composition of claim 1, wherein the amount of the crosslinking agent is within + / - 3 weight percent of the amount of the chain transfer agent.

9. The composition of any one of claims 1 to 8, further comprising at least one UV initiator.

10. 10. The composition of any one of claims 1 to 9, comprising 80 to 90 weight percent of said multi-stage soft acrylic resin and 10 to 20 weight percent of said branched polymer, based on the total weight of the composition.

11. A film comprising a layer of the composition according to any one of claims 1 to 10.

12. 12. The film of claim 11 having a thickness of 150 microns or less.

13. 13. The film of claim 11 or 12, which is transparent and does not exhibit crease whitening.

Citation Information

Patent Citations

  • Methyl methacrylate-based resin composition and its molded product

    JP1998259287A

  • Water-borne polymers with pendant allyl groups

    JP1999503777A

  • Multi-step polymer composition and film made from this composition

    JP2015532674A

  • Highly processable soft acrylic resin

    JP2022527777A

  • Highly processable multi-stage soft acrylic resins and methods for making same

    JP2022527778A